Application of Peer Teaching in Training Students to Teach Japanese (Mogi Jugyou) in Microteaching Courses - Herniwati, Herniwati; Judiasri, Melia Dewi; Funaki, Noa (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
This study aims to describe students' use of the peer teaching method in carrying out Japanese teaching practice (mogi jugyou) in microteaching courses. The peer teaching-learning method is a cooperative learning strategy for mutual respect, mutual understanding of the role given, having active and cooperative tendencies, and provides an assessment or evaluation after the teaching process is complete. This study aims to apply peer teaching in Japanese teaching practice (mogi jugyou) for third-year Japanese language education students in microteaching courses. The research method used was quasi-experimental research carried out on 3rd-degree (6th Semester) students with a total of 32 people. The initial stage is to plan teaching practice activities (mogi jugyou), implementation, and process observation of Japanese language teaching activities (mogi jugyou) in class and from teaching videos. The results of the study conclude that peer teaching is expected to make it easier for students to practice teaching Japanese in front of their classmates. Students were able to participate actively and are able to solve problems together using Japanese language teaching practice (mogi jugyou) during lectures. With peer teaching, students are able to practice teaching effectively, and the objectives and goals of the Japanese language learning materials provided can be achieved. It was also concluded that students have higher confidence when teaching students at schools, especially during PLSP.